Clinical role of CYP2C19 polymorphisms in patients with congenital adrenal hyperplasia due to 21-hydroxylase deficiency - Grošelj, Urh (Acta chimica slovenica, 2016)
Extraadrenal enzymes such as CYP2C19 may participate in residual 21-hydroxylation of progesterone leading to milder phenotypes of congenital adrenal hyperplasia (CAH) due to 21-hydroxylase deficiency (21OHD). Among 94 21OHD patients from the Slovene national registry 28 were homozygous or compound heterozygous for severe CYP21A2 mutations. We have reviewed their clinical phenotype and obtained information on maintenance doses of hydrocortisone and fludrocortisone. All patients were genotyped for CYP2C19*2 and CYP2C19*17 alleles. Among eleven patients with CYP2C19*1/*17 genotype, all had salt-wasting 21OHD. Out of 17 patients with CYP2C19 genotypes leading to normal or decreased CYP2C19 activity, 15 had salt-wasting, one had simple virilizing and one had non-classical 21OHD. CYP2C19*1/*17 genotype was associated with lower maintenance dose of fludrocortisone (p = 0.04), but not of hydrocortisone (p > 0.05). Increased CYP2C19 activity could slightly ameliorate mineralocorticoid deficiency in 21OHD.
Keywords: congenital adrenal hyperplasia; CYP21A2; CYP2C19; prirojena nadledvična hiperplazija